2021
DOI: 10.5664/jcsm.9476
|View full text |Cite
|
Sign up to set email alerts
|

Sleep is essential to health: an American Academy of Sleep Medicine position statement

Abstract: Sleep is a biological necessity, and insufficient sleep and untreated sleep disorders are detrimental for health, well-being, and public safety. Healthy People 2030 includes several sleep-related objectives with the goal to improve health, productivity, well-being, quality of life, and safety by helping people get enough sleep. In addition to adequate sleep duration, healthy sleep requires good quality, appropriate timing, regularity, and the absence of sleep disorders. It is the position of the American Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(130 citation statements)
references
References 65 publications
4
118
1
7
Order By: Relevance
“…Additionally, childhood cancer survivors indicated an unmet need and the difficulty they have finding fitting psychosocial care [ 77 ]. Our findings also confirm this for sleep disorders, which is comparable to low access to sleep care in the general population [ 10 , 36 ], and for adults who had cancer [ 78 ]. Helping childhood cancer survivors to find appropriate sleep treatment can fulfill this unmet need and improve their quality of life [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, childhood cancer survivors indicated an unmet need and the difficulty they have finding fitting psychosocial care [ 77 ]. Our findings also confirm this for sleep disorders, which is comparable to low access to sleep care in the general population [ 10 , 36 ], and for adults who had cancer [ 78 ]. Helping childhood cancer survivors to find appropriate sleep treatment can fulfill this unmet need and improve their quality of life [ 79 ].…”
Section: Discussionsupporting
confidence: 85%
“…In a longitudinal community-based study following children and adolescents, the presence of a sleep problem increased the chance of reporting a new medical disorder and new medication use in follow-up [ 1 ]. Recently, the American Academy of Sleep Medicine published a position paper about the essential role of sleep for health [ 10 ] and they stated that the importance of sleep should be more acknowledged within research, clinical care, in hospital sleeping conditions, and in educational programs for health professionals. For example, in a study among children and adolescents in primary care, it was found that sleep disorders were fairly underdiagnosed [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep is a biological function, an active behavior, crucial and vital for brain health and wellbeing at any age. It influences health status, quality of life, functioning, autonomy, and safety [7]. Indeed, recent findings suggest that good sleepers remain cognitively preserved for longer, report reduced rates of psychiatric diseases, and have a higher average life expectancy [8].…”
Section: Of 17mentioning
confidence: 99%
“…Sleep is an essential biological function that has many roles in maintaining the health of an organism, and better sleep quality is beginning to be emphasized in education and medicine ( Eban-Rothschild et al, 2017 ; Ramar et al, 2021 ). The amount of time adults sleep has decreased since the 1940s, leading the CDC to classify insufficient sleep as a public health epidemic ( CDC, 2015 ).…”
Section: Introductionmentioning
confidence: 99%